Carbonic anhydrase IV (CAR4) is expressed on IL-5 activated murine eosinophils - Wen, Ting (2014)
Eosinophilia and its cellular activation are hallmark features of asthma, as well as other allergic/T(H)2 disorders, yet there are few, if any, reliable surface markers of eosinophil activation. We have employed a FACS-based genome-wide screening system to identify transcriptional alterations in murine lung eosinophils recruited and activated by pulmonary allergen exposure. Using a relatively stringent screen with false-positive correction, we identified 82 candidate genes that could serve as eosinophil activation markers and/or pathogenic effector markers in asthma. Carbonic anhydrase IV (Car4) was a top dysregulated gene with 36-fold induction in allergen-elicited pulmonary eosinophils, which was validated by quantitative PCR, IHC and by flow cytometry. Eosinophil CAR4 expression was kinetically regulated by IL-5 but not IL-13. IL-5 was both necessary and sufficient for induction of eosinophil CAR4. While CAR4-deficient mice did not have a defect in eosinophil recruitment to the lung nor a change in eosinophil pH-buffering capacity, allergen-challenged chimeric mice that contained Car4(−/−) hematopoietic cells aberrantly expressed a series of genes enriched in biological processes involved in epithelial differentiation, keratinization, and anion exchange. In conclusion, we have determined that eosinophils express CAR4 following IL-5 or allergen exposure, and that CAR4 is involved in regulating the lung transcriptome associated with allergic airway inflammation; as such, CAR4 has potential value for diagnosing and monitoring eosinophilic responses.